Utilização de simulações de monte carlo para o cálculo da estimativa de incerteza na detecção eletroquímica de ácido úrico em amostras de plasma - Dadamos, Tony Rogério De Lima [UNESP]; Damaceno, Airton Juliano [UNESP]; Fertonani, Fernando Luis [UNESP]; Bettencourt Silva, Ricardo Jorge Neves (My University, 2018)
This work presents a low cost, simple and adequately reliable electrochemical alternative for the determination of uric acid in human serum in comparison to the enzymatic colorimetric reference method. The quality of the electrochemical measurements was assessed by comparing its uncertainty with a target value of 0.56 mg dL-1 and the measurements were carried out by the standard addition method. The modified working electrode consists of 25% lignin, 60% nanocarbon, 15% mineral oil and electrodeposited metallic copper. The uncertainty of measurement was estimated by the bottom-up approach, from which uncertainty components were combined by applying the uncertainty propagation law (LPI), the numerical method of Kragten and the Monte Carlo Simulation Method (MCM). The analytical procedure was successfully applied in the analysis of physiological sera added at 1.0, 3.0, 5.0, 7.0 and 9.0 mg dL-1 of AU and for two other samples of human saline. The results of the measurements carried out for the different serum samples using the proposed method, associated to the different methods for estimating the uncertainty, showed sufficiently low and metrologically equivalent values, in which the results were shown to be compatible with the estimated reference values.
Use of monte carlo simulations for the calculation of the uncertainty estimate in the electrochemical detection of uric acid in plasma samples
Keywords: Clinical Analyzes; Measurement Uncertainty; Monte Carlo Simulations